The effects and challenges of vocational training in Korea. (5th July 2019) - Lee, Jong-Wha; Han, Jong-Suk; Song, Eunbi
ABSTRACT: This paper explores whether training programs were effective in improving labor market performance of individuals, in particular wages and employment probability, in South Korea. The regression analyses using the data from Korean respondents in the Program for the International Assessment of Adults Competencies (PIAAC) survey show the strong positive effects of vocational training programs on earnings as well as on employment probability of individuals, while controlling for education, experience, and literacy skills as a proxy for unobserved ability, as well as occupation and industry. Moreover, the effects of job-training tend to be larger in older cohorts. These results suggest that against challenges posed by rapidly aging population and emergence of technological breakthroughs, Korea should promote vocational training activities and life-long learning programs, especially to the elderly.